Registros Alternativos de Saberes Culturais - Carmen Maria Aguiar; Maria Rosa Rodrigues Martins de Camargo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The present study treat about a characterization of writing some experience realized on specify and particular situations, involving, what can be considerate writing "adventure", people that don't have habit to write, and that realize themselves tempting, or with big needs to execute the task that need the utilization of a written code. In these occasions, many times they express their ideas and the world lived interpretation, mixing letters, words, and social representations, elaborated with alternatives codes of informations register - common practice in socials universes were the reading and writing are uncommon practices, like, in particular place were there is illiteracy predominance, involving a big contingent of excluded people of the school. This exclusion to bring this people for situations were they can be use just alternative mechanisms, created as to informations register about theirs history as for representations of daily situations.